Modified negative electrode material coating granulation method

By combining lithium zirconate and graphene with raw materials coke and asphalt, and using the modified negative electrode material coating and granulation method, the problems of low first discharge efficiency and poor circulation performance of the negative electrode material of lithium-ion battery are solved, and the electrode performance is significantly improved.

CN119551716APending Publication Date: 2025-03-04NINGXIA BAICHUAN NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411736918.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The first discharge efficiency and poor circulation performance of existing lithium-ion battery negative electrode materials are low.

Method used

The modified negative electrode material is prepared by combining lithium zirconate and graphene with raw material coke and asphalt, and superfine pulverization, pretreatment, heating coating and high-temperature cracking.

Benefits of technology

The first discharge efficiency and cycling performance of the electrode are significantly improved, and the conductive and mechanical properties of the material are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of negative electrode materials, in particular to a modified negative electrode material coating granulation method which comprises the following steps: preparing lithium zirconate, graphitizing raw material coke, mixing the raw material coke and the lithium zirconate, performing ultrafine crushing, performing pretreatment, performing ultrafine crushing on coated asphalt, and performing heating coating granulation on the raw material coke and the lithium zirconate by the coated asphalt. And carrying out high-temperature cracking on the surface of the coated granular material to form graphene. According to the negative electrode material, the raw material coke and the asphalt serve as basic raw materials, the material is modified through the lithium zirconate and the graphene, the preparation process is simple, the preparation scheme is clear and definite, the graphene is formed on the surface of the asphalt through a high-temperature cracking method, the mechanical and conductive performance of the electrode material can be effectively improved, and the lithium zirconate and the raw material coke are combined, so that the electrode material is prepared. The pre-lithiation treatment can effectively improve the first discharge efficiency of the electrode material, strengthen the cycle performance of the electrode material, and effectively improve the use effect of the electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of negative electrode material preparation, and in particular to a modified negative electrode material coating granulation method. Background Art

[0002] With the development of the automobile industry and the increasing consumption of non-renewable fossil fuels such as oil and natural gas, environmental protection and energy issues are becoming increasingly acute. In order to solve energy problems and achieve low-carbon and environmental protection, power batteries have made great progress. Power batteries include lithium-ion batteries, lead-acid batteries, and fuel cells. Among them, lithium-ion batteries have become the current development focus due to their advantages such as high specific energy, high specific power, low self-discharge, long service life and good safety. Graphite materials for lithium-ion battery negative electrode materials have the advantages of low lithium insertion / deinsertion potential, suitable reversible capacity, abundant resources and low price, but they also have disadvantages such as low first discharge efficiency and poor cycle performance, which affect the use effect of graphite materials.

[0003] Graphene is a single-layer hexagonal honeycomb lattice structure. Due to its unique chemical bonding method and large specific surface area, graphene materials have excellent mechanical properties, thermal properties and conductive properties; lithium zirconate material is a material with excellent stability and high lithium ion transmission performance; modifying graphite materials with graphene and lithium zirconate materials has great practical significance. Summary of the invention

[0004] In view of the above problems, the present invention provides a modified negative electrode material coating granulation method to solve the problems of low first discharge efficiency and poor cycle performance of the electrode in the prior art.

[0005] To achieve the above object, the present invention provides a modified negative electrode material coating granulation method, comprising the following steps:

[0006] S1: adding an ethanol solvent to a stirring kettle, adding a lithium source and a zirconium source to the ethanol solvent, stirring evenly to form a mixed solution, adding acetonitrile to the mixed solution, heating and continuously stirring to obtain a white colloidal lithium zirconate precursor;

[0007] S2: drying the lithium zirconate precursor, placing the dried lithium zirconate precursor in a calcining furnace and calcining it in an air atmosphere to obtain white lithium zirconate powder;

[0008] S3: sending the raw coke into a rotary kiln for drying, controlling the moisture and volatile matter in the raw coke, and graphitizing the raw coke in a graphitization furnace under an inert atmosphere;

[0009] S4: mixing the raw coke with the lithium zirconate powder, and ultra-finely grinding the mixture of the raw coke and the lithium zirconate to obtain a mixed powder, wherein the average particle size D50 of the mixed powder is 8 to 20 μm;

[0010] S5: pretreating the mixed powder in a pretreatment kettle;

[0011] S6: ultrafinely crushing the coated asphalt to obtain asphalt powder, wherein the average particle size D50 of the asphalt powder is 1 to 10 μm;

[0012] S7: fully mixing the mixed powder and the asphalt powder in a mixing kettle, placing the mixed powder and the asphalt powder in a coating kettle for heating and coating to obtain coated pellets, wherein the particle size of the coated pellets is controlled to be 20 to 50 μm;

[0013] S8: Mix the coated pellets and the phthalocyanine compound evenly, place them in an atmosphere furnace, and heat the mixed coated pellets and phthalocyanine compound under the protection of an inert atmosphere. After the heating is completed, cool them down naturally, and part of the asphalt on the surface of the coated pellets is cracked into graphene material attached to the surface of the coated pellets, thereby finally obtaining a modified negative electrode material.

[0014] Furthermore, in S1, the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium acetate and lithium dihydrogen phosphate; the zirconium source is one or more of zirconium nitrate pentahydrate, hydrated zirconium oxynitrate, zirconium sulfate and zirconium phosphate; the molar ratio of lithium to zirconium in the lithium source and the zirconium source is 2.0-2.3:1; the total amount of the lithium source and the zirconium source added is 20%-60% of the ethanol solvent; the amount of acetonitrile added is 1%-10% of the ethanol solvent; and the heating temperature is 50-100°C.

[0015] Furthermore, in S2, the drying temperature of the lithium zirconate precursor is 100-200°C, the calcination temperature is 600-800°C, and the calcination time is 4-10 hours.

[0016] Furthermore, in S3, the drying temperature of the raw coke is 100-200°C, the moisture content in the raw coke is controlled to be 1-4%, the volatile matter is ≤7%, and the graphitization temperature is 2500-3300°C.

[0017] Furthermore, in S4, the raw coke includes one or more of needle coke, petroleum coke and asphalt coke, and the mass ratio of the lithium zirconate powder to the raw coke is 1:80-150.

[0018] Furthermore, in S5, the pretreatment temperature of the mixed powder is 200-400° C., and the pretreatment time is 2-4 hours.

[0019] Furthermore, in S7, the mass ratio of the asphalt powder to the mixed powder is 6-10:100, the heating temperature of the coating process is 400-750° C., and the coating time is 2-4 hours.

[0020] Furthermore, in S8, the mass ratio of the phthalocyanine compound to the coated pellets is 3 to 8:100, the inert atmosphere includes one of nitrogen and argon, the heating process of the coated pellets and the phthalocyanine compound is gradually heated at a rate of 5 to 10°C per minute, and when the temperature reaches 300, 400, and 500°C, it is kept warm for 2 to 3 hours, and when the temperature reaches 1000°C, it is kept warm for 8 to 12 hours.

[0021] Beneficial effects of the present invention:

[0022] The negative electrode material of the present invention uses raw coke and asphalt as basic raw materials, and uses lithium zirconate and graphene to modify the material. The preparation process is simple, the preparation scheme is clear and definite, and the conductive property of the material is effectively improved, the first discharge efficiency of the electrode is improved, and the cycle performance is enhanced.

[0023] In the present invention, phthalocyanine compounds are added to the coated granules to form a hollow structure in the coating layer, which facilitates the migration of lithium ions in the coating layer, thereby improving the discharge efficiency of the electrode and enhancing the conductive performance;

[0024] In the present invention, graphene is formed on the surface of asphalt by high-temperature pyrolysis, and graphene can effectively increase the migration speed of lithium ions and electrons, thereby further improving the mechanical and conductive properties of the electrode material;

[0025] In the present invention, lithium zirconate is combined with raw material coke, and the negative electrode material prepared by pre-lithiation operation can greatly improve the conductive performance of the material. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Embodiment 1

[0028] The asphalt-coated graphite material is modified with lithium zirconate and graphene at the same time. The specific steps are as follows:

[0029] S1: adding an ethanol solvent to a stirred tank, adding lithium carbonate and zirconium nitrate pentahydrate to the ethanol solvent, wherein the molar ratio of lithium to zirconium is 2:1, stirring evenly to form a mixed solution, adding 5% acetonitrile to the mixed solution, heating at 80° C. and continuously stirring, to obtain a white colloidal lithium zirconate precursor;

[0030] S2: drying the lithium zirconate precursor at a drying temperature of 150° C., placing the dried lithium zirconate precursor in a calcining furnace and calcining it in an air atmosphere at a temperature of 700° C. for 6 hours to obtain a white lithium zirconate powder;

[0031] S3: sending the raw coke into a rotary kiln for drying at a drying temperature of 100-200° C., controlling the moisture content of the raw coke to be 4% and the volatile matter content to be 7%, and graphitizing the raw coke in an inert atmosphere using a graphitization furnace at a graphitization temperature of 3000° C.;

[0032] S4: mixing needle coke and lithium zirconate powder in a ratio of 100:1, ultrafinely grinding the mixture of needle coke and lithium zirconate to obtain a mixed powder, wherein the average particle size D50 of the mixed powder is 8 to 20 μm;

[0033] S5: pretreating the mixed powder in a pretreatment kettle, stirring the mixed powder at high speed to remove volatiles, and heating the mixed powder at a heating temperature of 300° C. for 4 hours;

[0034] S6: ultrafinely crushing the coated asphalt to obtain asphalt powder, wherein the average particle size D50 of the asphalt powder is 1 to 10 μm;

[0035] S7: fully mix the mixed powder and the asphalt powder in a mixing kettle at a ratio of 100:10, place the mixed powder and the asphalt powder in a coating kettle for heating and coating, the heating temperature is 750°C, the coating time is 4 hours, and coated pellets are obtained, the particle size of the coated pellets is controlled to be 20-50 μm;

[0036] S8: The coated pellets and phthalocyanine tubes are mixed in a mass ratio of 100:8. After the mixture is evenly mixed, it is placed in an atmosphere furnace. Under the protection of argon, the mixed coated pellets and copper phthalocyanine are heated. The temperature is gradually increased at a rate of 5°C per minute during the heating process. When the temperature reaches 300, 400, and 500°C, it is kept warm for 2 hours. When the temperature reaches 1000°C, it is kept warm for 12 hours. After the heating is completed, the temperature is naturally cooled. Part of the asphalt on the surface of the coated pellets is cracked into graphene material attached to the surface of the coated pellets, and finally the negative electrode material is obtained, which is recorded as graphiteGZ-1.

[0037] Embodiment 2

[0038] In this embodiment, only lithium zirconate is used to modify the asphalt-coated graphite material, and the remaining steps refer to the first embodiment to obtain the negative electrode material graphite Z-2.

[0039] Embodiment 3

[0040] In this embodiment, only the asphalt-coated graphite material is modified with graphene, and the remaining steps refer to the first embodiment to obtain the negative electrode material graphite G-3.

[0041] Embodiment 4

[0042] In this embodiment, asphalt-coated graphite material is prepared without using lithium zirconate and graphene modification. The remaining steps refer to the first embodiment to obtain the negative electrode material graphite-4.

[0043] The negative electrode materials in Examples 1 to 4 were used to make negative electrodes of lithium batteries, and charge and discharge tests were performed. The experimental results are shown in Table 1 below:

[0044] Table 1

[0045]

[0046] In summary, by comparing and analyzing the negative electrodes made of the materials prepared in Examples 1 to 4, it can be seen that the electrical properties of the electrode material modified with both lithium zirconate and graphene are better than those of the electrode material modified with either lithium zirconate or graphene alone, and better than those of the electrode material not subjected to modification.

[0047] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A modified negative electrode material coating granulation method, characterized in that: The steps include: S1: adding an ethanol solvent to a stirring kettle, adding a lithium source and a zirconium source to the ethanol solvent, stirring evenly to form a mixed solution, adding acetonitrile to the mixed solution, heating and continuously stirring to obtain a white colloidal lithium zirconate precursor; S2: drying the lithium zirconate precursor, placing the dried lithium zirconate precursor in a calcining furnace and calcining it in an air atmosphere to obtain white lithium zirconate powder; S3: sending the raw coke into a rotary kiln for drying, controlling the moisture and volatile matter in the raw coke, and graphitizing the raw coke in a graphitization furnace under an inert atmosphere; S4: mixing the raw coke with the lithium zirconate powder, and ultra-finely grinding the mixture of the raw coke and the lithium zirconate to obtain a mixed powder, wherein the average particle size D50 of the mixed powder is 8 to 20 μm; S5: pretreating the mixed powder in a pretreatment kettle; S6: ultrafinely crushing the coated asphalt to obtain asphalt powder, wherein the average particle size D50 of the asphalt powder is 1 to 10 μm; S7: fully mixing the mixed powder and the asphalt powder in a mixing kettle, placing the mixed powder and the asphalt powder in a coating kettle for heating and coating to obtain coated pellets, wherein the particle size of the coated pellets is controlled to be 20 to 50 μm; S8: Mix the coated pellets and the phthalocyanine compound evenly, place them in an atmosphere furnace, and heat the mixed coated pellets and phthalocyanine compound under the protection of an inert atmosphere. After the heating is completed, cool them down naturally, and part of the asphalt on the surface of the coated pellets is cracked into graphene material attached to the surface of the coated pellets, thereby finally obtaining a modified negative electrode material.

2. A negative electrode material coating granulation method according to claim 1, characterized in that: In S1, the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium acetate and lithium dihydrogen phosphate; the zirconium source is one or more of zirconium nitrate pentahydrate, hydrated zirconium oxynitrate, zirconium sulfate and zirconium phosphate; the molar ratio of lithium to zirconium in the lithium source and the zirconium source is 2.0-2.3:1; the total amount of the lithium source and the zirconium source added is 20%-60% of the ethanol solvent; the amount of acetonitrile added is 1%-10% of the ethanol solvent; and the heating temperature is 50-100°C.

3. A negative electrode material coating granulation method according to claim 1, characterized in that: In S2, the drying temperature of the lithium zirconate precursor is 100-200°C, the calcination temperature is 600-800°C, and the calcination time is 4-10 hours.

4. A negative electrode material coating granulation method according to claim 1, characterized in that: In S3, the drying temperature of the raw coke is 100-200°C, the moisture content of the raw coke is controlled to be 1-4%, the volatile matter is ≤7%, and the graphitization temperature is 2500-3300°C.

5. A negative electrode material coating granulation method according to claim 1, characterized in that: In S4, the raw coke includes one or more of needle coke, petroleum coke and pitch coke, and the mass ratio of the lithium zirconate powder to the raw coke is 1:80-150.

6. A negative electrode material coating granulation method according to claim 1, characterized in that: In S5, the pretreatment temperature of the mixed powder is 200-400° C., and the pretreatment time is 2-4 hours.

7. A negative electrode material coating granulation method according to claim 1, characterized in that: In S7, the mass ratio of the asphalt powder to the mixed powder is 6-10:100, the heating temperature of the coating process is 400-750° C., and the coating time is 2-4 hours.

8. A negative electrode material coating granulation method according to claim 1, characterized in that: In S8, the mass ratio of the phthalocyanine compound to the coated pellets is 3 to 8:100, the inert atmosphere includes one of nitrogen and argon, the heating process of the coated pellets and the phthalocyanine compound is gradually heated at a rate of 5 to 10°C per minute, and when the temperature reaches 300, 400, and 500°C, it is kept warm for 2 to 3 hours, and when the temperature reaches 1000°C, it is kept warm for 8 to 12 hours.